EFFICACY AND SAFETY OF A NEW COMBINED MEDICATION WITH RECOMBINANT INTERFERON AND BETAMETHASONE IN THE TREATMENT OF HAY FEVER DURING PERIODS OF EXACERBATION - A. A. Ryabtseva; N. Y. Sotnikova; O. V. Chumikov; N. A. Stupakova (Oftalʹmologiâ)
Objective: to assess the efficacy, safety and tolerability of the new combined medication Allergoferon® beta in patients with moderate-to-severe hay fever (seasonal allergic rhinitis and conjunctivitis) during periods of exacerbation. patients and methods: the object of our study was medication Allergoferon® beta (recombinant human interferon alpha-2b, not less than 5000 IU/ml + betamethasone sodium phosphate, 1.0 mg/ml) in the form of eye and nasal drops. Total of 120 patients aged 18-65 years with hay fever for at least two years were enrolled in the clinical trial, including 76 women and 44 men. All patients had a clinical picture of moderate-to-severe hay fever during periods of exacerbation. Patients were divided into two equal groups. The main group received Allergoferon® beta, the control group was treated with Oftan® Dexamethasone and Nasobek medications. This trial used a randomized, open-label, multicenter, parallel, comparative, controlled study design. results: we found that new combined medication Allergoferon® beta had a significant therapeutic effect in relieving main clinical manifestations of acute hay fever and showed a higher efficacy, than the comparison remedies. By comparing similar symptoms in both groups, we observed that in patients treated with Allergoferon® beta clinical symptoms of acute hay fever were relieved earlier (on the 5th day of treatment), than in the control group (on the 10th day of treatment) and the disease itself proceeded milder. Therapeutic efficacy of Allergoferon® beta was 85,96% (in the control group — 74,73%, p<0.05). During clinical trial we have not observed any adverse effects; general or local toxic and allergic reactions were also not discovered. The medication tolerability was rated as “good” for patients. Conclusion: according to the clinical study results, the medication Allergoferon® beta (eye and nasal drops) is recommended for the state registration and can be used by medical professionals in the treatment of moderate-to-severe hay fever (seasonal allergic rhinitis and conjunctivitis), including periods of exacerbation.